2014
DOI: 10.4330/wjc.v6.i4.130
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia is a key factor in the management of stable coronary artery disease

Abstract: Previous studies demonstrated that coronary revascularization, especially percutaneous coronary intervention (PCI), does not significantly decrease the incidence of cardiac death or myocardial infarction in patients with stable coronary artery disease. Many studies using myocardial perfusion imaging (MPI) showed that, for patients with moderate to severe ischemia, revascularization is the preferred therapy for survival benefit, whereas for patients with no to mild ischemia, medical therapy is the main choice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…Most of the studies supporting the PSS have included lesions with trivial or disease-free SB [9][10][11][12][13]. For patients with no to mild ischemia, medical therapy is the treatment of choice and revascularization is associated with increased mortality [14]. For this reason, the PSS can be preferable to a systematic 2SS for lesions with small and/or non-diseased SB.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies supporting the PSS have included lesions with trivial or disease-free SB [9][10][11][12][13]. For patients with no to mild ischemia, medical therapy is the treatment of choice and revascularization is associated with increased mortality [14]. For this reason, the PSS can be preferable to a systematic 2SS for lesions with small and/or non-diseased SB.…”
Section: Discussionmentioning
confidence: 99%
“…17 The extent of myocardial ischemia is a key factor in the management and prognosis of patients with stable CAD. 18 induce AMI. Therefore, the current study suggests a different risk stratification strategy for diabetic and non-diabetic patients.…”
Section: The Utility Of Ffr To Predict Eventsmentioning
confidence: 98%
“…Upon damage from ischemia, the heart undergoes extensive revascularization. 22 The pro-angiogenic effect of lixisenatide suggests that this agent may promote revascularization in the ischemiainjured heart. At the molecular level, we found that lixisenatide promoted the production of the anti-oxidative regulators Nrf2 and HO-1.…”
Section: Discussionmentioning
confidence: 99%